Implementation of the “Safinatun Najah” Textbook by Kh. Muhammad Hasan Genggong at MI Kholafiyah Syafi'iyah Zainul Hasan Genggong - Ahmad Zaini Al Ma'rufi; Ainur Rofiq Sofa (Al-Madrasah: Jurnal Ilmiah Pendidikan Madrasah Ibtidaiyah, 2026)
The learning of the Safīnatun Najāh text represents an integration of pesantren-based education within the elementary curriculum of MI Kholafiyah Syafi'iyah Zainul Hasan Genggong. This study aims to describe the implementation of teaching this text in the fifth grade and to identify its impact on student learning outcomes. The research employed a descriptive qualitative approach with data collected through observation, interviews, and documentation. Data analysis was carried out through data reduction, data presentation, and conclusion drawing. The findings indicate that the teaching of Safīnatun Najāh is conducted through several stages, namely qirā'ah (textual reading), tarjamah (vocabulary meaning comprehension), and syarḥ al-ma'nā (interpretation and content elaboration). The methods used include lecture, question and answer, discussion, memorization, and practical application. The learning process is not merely theoretical but emphasizes habituation in students' daily religious practices. Its impact can be seen in students' improved understanding of basic jurisprudence, particularly in the chapters on purification, prayer procedures, and Islamic etiquette. Supporting factors include the school's religious environment and teachers' competence in classical Islamic texts. The main challenge is the varying ability of students to read Arab gundul (unvocalized Arabic script), which is addressed through intensive guidance and repeated practice. Overall, this instructional approach effectively fosters religious understanding and character formation among students.